An Efficient, Large-Scale Survey of Hepatitis C Viremia in the Democratic Republic of the Congo Using Dried Blood Spots. (18th October 2017) - Parr, Jonathan B; Lodge, Evans K; Holzmayer, Vera; Pepin, Jacques; Frost, Eric H; Fried, Michael W; McGivern, David R; Lemon, Stanley M; Keeler, Corinna; Emch, Michael; Mwandagalirwa, Kashamuka; Tshefu, Antoinette; et al.
Abstract : Hepatitis C viral load testing using dried blood spots reliably identifies candidates for treatment and is easily incorporated into large-scale surveys, including those conducted in resource-limited settings such as the Democratic Republic of the Congo. Abstract: Background: Efficient viral load testing is needed for hepatitis C (HCV) surveillance and diagnosis. HCV viral load testing using dried blood spots (DBSs), made with a single drop of finger-prick whole blood on filter paper, is a promising alternative to traditional serum- or plasma-based approaches. Methods: We adapted the Abbott Molecular m 2000 instrument for high-throughput HCV viremia testing using DBSs with simple specimen processing and applied these methods to estimate the national burden of infection in the Democratic Republic of the Congo (DRC). We tested DBSs collected during the 2013–2014 DRC Demographic and Health Survey, including 1309 adults ≥40 years of age. HCV-positive samples underwent targeted sequencing, genotyping, and phylogenetic analyses. Results: This high-throughput screening approach reliably identified HCV RNA extracted from DBSs prepared using whole blood, with a 95% limit of detection of 1196 (95% confidence interval [CI], 866–2280) IU/mL for individual 6-mm punches and 494 (95% CI, 372–1228) IU/mL for larger 12-mm punches. Fifteen infections were identified among samples from the DRC Demographic and Health Survey; the weighted country-wide prevalence of HCV viremia was 0.9% (95% CI, 0.3%–1.6%) among adults ≥40 years of age and 0.7% (95% CI, .6%–.8%) among human immunodeficiency virus–infected subjects. All successfully genotyped cases were due to genotype 4 infection. Conclusions: DBS-based HCV testing represents a useful tool for the diagnosis and surveillance of HCV viremia and can easily be incorporated into specimen referral systems. Among adults ≥40 years of age in the DRC, 100000–200000 may have active infection and be eligible for treatment.